Novel Lactic Acid Bacteria Strains from Regional Peppers with Health-Promoting Potential - Nuñez, Ivana Micaela (2024)
This study provides a comprehensive investigation of lactic acid bacteria (LAB) isolatedfrom Argentinean Capsicum annum L. This research covers important aspects, including genotypiccharacterization, bacterial stress tolerance, adhesion ability, safety evaluation, and functional andtechnological properties. The predominant isolates were identified as Lactilactobacillus curvatusand Lactiplantibacillus plantarum. A Rep-PCR analysis grouped the isolates into 11 clonal groups.Lp. plantarum LVP 40 and LV 46, Levilactobacillus brevis LVP 41, Pediococcus pentosaceus LV P43, and Lt. curvatus LVP44 displayed both safety and resilience against adverse conditions such as a slow pH, bile, and simulated gastric and intestinal juices. Moreover, the LAB strains exhibited highhydrophobicity and auto-aggregation percentages, NaCl tolerance, and a substantial acidifyingcapacity. LAB supernatants demonstrated promising surfactant and emulsifying properties. Likewise, they differentially inhibited Staphylococcus aureus and Pseudomonas aeruginosa biofilms, showcasing their potential as antipathogenic agents. Noteworthily, some strains displayed considerable congregation with these pathogens, and several isolates showed an effective antimutagenic and detoxifying power, further emphasizing their multifaceted capabilities. Five pepper bacterial strains showcased beneficial properties, suggesting their potential for gut health enhancement. In summary, these LAB strains hold promise as vegetable fermentation starters, contributing to food safety and versatile applications in food science.